Chronotopes of law jurisdiction, scale, and governance - Valverde, Mariana 1955- (Social justice, 2015)
"Jurisdiction, Scale and Governance: Chronotopes of Law develops a post-metaphysical framework for analyzing the spatio-temporal workings of law and other forms of governance. In this regard, it does not seek merely to combine analyses of legal temporality carried out by anthropologists with analyses of law and space carried out by geographers and socio-legal scholars. Adding two metaphysical abstractions together does not produce anything but somewhat more complex, but equally metaphysical, abstractions. After Kant, 'time' and 'space' are simply categories of human understanding, not metaphysical entities. And, in this book Mariana Valverde develops an anti-metaphysical theoretical approach to law that aims not to theorize the world in general, but rather to be useful to researchers who seek to shed light on the actual workings of law and other forms of governance. Written by one of the foremost theorists in the area, this theoretically innovative work constitutes a major contribution to contemporary studies in law and society. "..